2021
DOI: 10.1002/anie.202101474
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Catabolic Multifunctional DNAzyme Nanosponge for Programmable Drug Delivery and Efficient Gene Silencing

Abstract: DNAzyme‐based gene therapy holds immense prospects for effectively treating severe diseases, yet is constrained with inefficient delivery and unconditional activation. Herein, we designed a bioinspired self‐catabolic DNA nanocapsule for sustaining tumor‐specific cascade activation of therapeutic DNAzyme. The exquisite DNAzyme was temporarily masked by the self‐excising DNAzyme in the hierarchical rolling circle replication (RCR) nanostructures, thus stayed in an inactive state in physiological fluids. Through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 73 publications
0
75
0
Order By: Relevance
“…DNA could form hybrid nanomaterials with different moieties including inorganic NPs (Huo et al, 2019), mineral salt (Wang et al, 2021), and metal ions (Li M. et al, 2019). These DNAinorganic hybrids are usually conjugated or electrostatically adsorbed with nucleic acid drugs (Singh et al, 2010).…”
Section: Dna-inorganic Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA could form hybrid nanomaterials with different moieties including inorganic NPs (Huo et al, 2019), mineral salt (Wang et al, 2021), and metal ions (Li M. et al, 2019). These DNAinorganic hybrids are usually conjugated or electrostatically adsorbed with nucleic acid drugs (Singh et al, 2010).…”
Section: Dna-inorganic Nanomaterialsmentioning
confidence: 99%
“…The DNA nanoflower effectively inhibits HIF-1α protein expression, demonstrating efficient HIF-1α antisense DNA delivery via DNA nanoflower. Wang et al (2021) reported a bioinspired self-catabolic DNA nanosponge for efficient gene silencing via the rolling circle replication (RCR) (Figure 3C). The therapeutic DNAzyme (tDNAzyme) and self-motivated DNAzyme were designed as a template of RCR.…”
Section: Dna-inorganic Nanomaterialsmentioning
confidence: 99%
“…5 In particular, DNAzymes have been identified as prominent therapeutic tactic that successively catalyze the hydrolysis of oncogene mRNAs without kidnapping their cellular machinery. [6][7][8][9] Moreover, another superiority of DNAzymes to commonly used siRNA is their high stability, multiple turnover rate yet low off-target effect. [10][11][12][13] Despite these advantages, DNAzyme-based gene therapy in tumors is still in its infancy stage of scientific research and restrained by controllable and exclusive activation in cancer cells while avoiding undesired cytotoxicity in normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…We postulate that the multi-step requirement can be avoided via the use of DNA nanoflowers (DNA NFs), microsized, flower-shaped DNA assemblies. [9] Because they are prepared through rolling circle amplification (RCA), each DNA NF contains a massive number of repeating sequences that can hybridize with another complementary DNA. [10] They are easy to synthesize and highly stable, [9] and more importantly for this study, they do not move on paper surface under lateral flow settings.…”
mentioning
confidence: 99%
“…[9] Because they are prepared through rolling circle amplification (RCA), each DNA NF contains a massive number of repeating sequences that can hybridize with another complementary DNA. [10] They are easy to synthesize and highly stable, [9] and more importantly for this study, they do not move on paper surface under lateral flow settings. [11] Therefore, DNA NFs can replace MBs to create a separation-free PTS assay, as we will demonstrate in this study.…”
mentioning
confidence: 99%